Determinants of temporary labour migration in southern India. Issue 3 (1st September 2016) - Dodd, Warren; Humphries, Sally; Patel, Kirit; Majowicz, Shannon; Dewey, Cate
ABSTRACT: We present new data from three village panchayats in northwest Tamil Nadu and investigate the associations between demographic and socioeconomic factors with temporary labour migration from this setting. Individual ( n  = 1110) and household ( n  = 278) level logistic regression models were used to demonstrate how factors at each of these levels can influence temporary labour migration trajectories. Young males were most likely to temporarily migrate for work from this region. Additionally, large households from historically disadvantaged castes with marginal land and housing were most likely to have at least one migrant member. Households with multiple migrant members appear to use temporary migration to cope with serious deprivation relative to households with only one migrant member. These findings provide a strong case that can be compared to other settings in India and can be used to inform improved policy and targeted development initiatives to support temporary migrant workers and their households.